Enhancement Of Producer Gas Quality Through Co2 Absorption Using Cao-Sand Mixture In A Fluidized Bed Reactor - Mohammud @ Mahmood, Mohd Mahadzir (2012)

(untitled)
This thesis concerns an experimental study and numerical simulation used to enhance the producer gas quality through carbon dioxide (CO2) absorption using calcium oxide (CaO) - sand mixture in a CO2 bubbling fluidized bed absorption reactor (CO2 BFBAR). Biomass gasification is a thermo-chemical conversion process of solid biomass into gaseous fuel called producer gas that can be used to generate power and electricity. However, carbon dioxide (CO2) content in the producer gas reduces its heating values as CO2 acts as a diluent. The use of limestone consisting mainly of the mineral calcite (calcium oxide, CaO) as calcium based sorbent to absorb CO2 in the producer gas will increase the heating value of the producer gas. 3-D Computational Fluid Dynamics (CFD) software was used to determine hydrodynamic characteristic of CaO-sand bed material in a CO2 BFBAR. The simulation results show that with 100, 500 and 1000 micron particle size of CaO, good fluidization at 15 – 55 L/min volume flow rate of air was achieved. The CO2 BFBAR was developed and the behavior of CaO-sand mixtures in a cold model experiment was studied. The effect of the CaO-sand mixtures, the CaO particle sizes, the volume flow rate and the pressure of air intake were investigated experimentally. The absorption-desorption process of CaO was studied with the thermogravimetric analyzer (TGA) over 1, 4 and a muticycle. Three differents temperature (500, 600 and 700oC) were set a variables. The reaction rate of CaO was obtained. Results show that for number 1 cycle the CO2 absorption xxv reaction rate was fast at first stage and then followed with slower reaction rate. About 0.337 and 0.065 mg/min CO2 reaction rate were obtained in rapid and slow absorption regime respectively. It is also observed that the CO2 absorption reaction rates decreases when number of cycle’s desorption-absorption process was increased. After TGA experiment, the hot model experiment was conducted to investigate CO2 absorption at the optimum condition obtained from the cold model experiment. The simulated gas consisting of 20% CO2 and 80% N2 was introduced in the CO2 BFBAR at temperatures of 650-750oC. The CaO percentages of 50 and 40 in sand were found to have a good fluidization at all air pressures (2 - 6 bar). In addition to that, the 1000 micron particle size of the CaO–sand mixture and the volume flow rate of air between 15 – 55 L/min were also found to generate good fluidization. In the hot model experiment, the best CO2 absorption occurs in 50% CaO mixture with simulated gas, at pressure of 3 bar and the volume flow rate of 45 L/min at 650-750oC in the CO2 BFBAR. The CO2 concentration in the simulated producer gas when applied decreases approximately 57.5%, where this resulted in increases of H2 and CO to approximately 12% and 6%, respectively within 10 minutes of operation. For the compressed producer gas, the CO2 concentration decreases approximately 77.4%, where H2 and CO increase approximately 23.3% and 21.7%, respectively. Therefore the heating value of the compressed producer gas increases from 4.51 to maximum of 6.04 MJ/Nm3 an increase of 38%.